Domains of adherence and non-adherence to anti-hypertensive medications in hypertensive patients from Kuala Lumpur: a qualitative study - Yew, Sheng-Qian; Tan, Kit-Aun; Mohd Nazan, Ahmad Iqmer Nashriq; Abdul Manaf, Rosliza (Faculty of Medicine and Health Sciences, 2023)
Introduction: Previous medication adherence studies primarily focused on the domains of non-adherence in hypertension treatment and less attention has been given on domains that encourage adherence to anti-hypertensive medications. The current study is aimed to identify the domains of adherence and non-adherence to anti-hypertensive medications among hypertensive patients in Kuala Lumpur, Malaysia. Methods: Hypertensive patients from two public health clinics in Kuala Lumpur were invited for in-depth interviews until thematic saturation. Audio recordings from these interviews were transcribed verbatim. Transcripts were then analysed deductively with the guidance of the World Health Organization Medication Adherence Framework to extract the domains of adherence and non-adherence to anti-hypertensive medications. Results: Ten patients who were predominantly Malays and aged 34-73 years old participated the study. Patient-related (encompassing knowledge, attitude, belief and culture, lifestyle, personal barriers, self-efficacy, and cue to action), socioeconomic (encompassing social support), condition-related (encompassing nature of illness and presence of multiple co-morbidities), therapy-related (encompassing experience of receiving treatment, barrier in treatment, and side effects of treatment), and healthcare system (encompassing access to healthcare and healthcare center experience) domains were identified as central to the medication-taking behaviour of hypertensive patients. Conclusion: Sixteen codes of adherence and 22 codes of non-adherence to anti-hypertensive medications were identified, which were distributed across five domains (patient-related, socioeconomic, condition-related, therapy related, and healthcare system domains). These findings can help to inform future development of medication adherence questionnaires, individualised interventions for patients with adherence problems, and targeted health promotion programmes to reduce uncontrolled hypertension